Korupsi Pertamax: Refleksi atas Krisis Integritas dan Kejujuran dalam Birokrasi Indonesia - Azwin Raynaldy Sinaga; Regi Pramesty Sariman Putri; Christiano Soeharto Hutauruk; Aisyah Aldina (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
Corruption in Indonesia has reached an alarming level, functioning not only as a legal violation but also as a reflection of a profound moral crisis within the bureaucracy. The term “Pertamax Corruption” refers to a high-level form of corruption—beyond the mere abuse of power—indicating a systemic erosion of honesty and public integrity. This crisis reveals that corrupt practices are no longer hidden; instead, they have become embedded in bureaucratic culture, legitimized through language, social behavior, and permissive public attitudes. This study employs a qualitative method through a literature review of academic journals, reports from anti-corruption institutions, and official government publications. The findings indicate that weak oversight mechanisms, entrenched patronage, and the decline of public ethics are key factors that sustain corruption in Indonesia. Restoring public trust requires moral reform through character education, exemplary leadership, and the reinforcement of integrity across all levels of bureaucracy.